Sustainable food security in modern framework for optimal nutritional well-being of Malaysians - Haque, A. K. M. Ahasanul; Jan, Muhammad Tahir; Rahman, Mohammad Moshiur (Mac Arts & Communication, 2023)
Food security is Malaysia’s second Sustainable Development Goal (SDG), which ensures access to nutritious food available for everyone in the country. In 2006, the Ministry of Health (MOH) launched NPANM II, the National Plan of Action for Nutrition of Malaysia, to handle food and nutrition issues. National surveys revealed that most Malaysians still cannot completely comprehend and implement the Food Pyramid into practice. The Ministry intends to continue the programme through NPANM III to advance the population’s health and strengthen food and nutrition security. Therefore, this empirical study aims to develop inclusive, sustainable food security in a modern framework to identify possible reasons affecting nutritional well-being. In the data collection phase, a questionnaire survey is administered among 318 respondents from five states, i.e. Selangor, Pinang, Johor, Kuantan, and Melaka. The data collection process was taken over three months, from January to March 2023, and it ensured the rectification of missing data. The results derived from the study would provide valuable insights to the policymakers towards identifying the most influential factors toward ensuring food security for enhancing the quality of health and well-being of the Malaysian population and have significant implications for achieving the objectives set under the NPANM III, 2016-2025.